Evolution of monetary integration: Case of the West African Monetary Zone - Ngozi Eunice Egbuna (West African Journal of Monetary and Economic Integration, 2018)
This paper attempts to examine the challenges of monetary integration in the West African Monetary Zone (WAMZ) during the period 2001-2017, within the framework of the Economic Community of West African States (ECOWAS) Monetary Cooperation Programme (EMCP). The paper recounts the evolution of monetary integration in the WAMZ by reviewing issues that impedes the attainment of the goals of the WAMZ and assessesing progress and achievements made. The paper draws on the conclusions of previous studies on ECOWAS and WAMZ monetary and economic integration programmes to present an overall view of the journey, so far, toward the introduction of a single currency in the Zone. The findings of this paper suggest that a lot of gains have been made on the WAMZ programme. However, the Zone continuous to face challenges bordering on asymmetric shocks and fiscal dominance. Low level of trade and weak policy implementation commitment in the Zone also adversely impacted the integration process. The paper concludes that more should be done to ensure that the required building blocks are put in place prior to the launching of the single currency and continued pursuance of convergence ex-post.
Keywords: E45; E52; F15; 330; Monetary Policy; Monetary Union; West African Monetary Zone